FORMULA FANTASI YANG TERCERMIN DALAM FILM HARRY POTTER AND THE GOBLET OF FIRE (2005) - Mangantar, Elvira R.; Wantasen, Isnawaty L.; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT          This research entitled Formula Fantasi Yang Tercermin dalam Film Harry Potter and The Goblet of Fire (2005) is written to fulfill the requirement of accomplishing bachelor’s degree in English Department Faculty of Humanities Sam Ratulangi University. The focus of this research is Fantasy Formula in the film. The problem of this research is focusing on what are the fantasy formula is and how the reflection of fantasy formula as reflected in the film Harry Potter and The Goblet of Fire (2005). The writer used theory from Cawelti (1976) and Snyder (2011) to analyze the fantasy formula. The result of this research shown that the Fantasy Formula as Reflected in Harry Potter and The Goblet of Fire (2005).Keywords: Fantasy, Formula, Film, Theory of Film, Mise-en-scene